Fresh complaint : stories - Eugenides, Jeffrey (Farrar, Straus and Giroux, 2017)
This collection presents characters in the midst of personal and national crises. We meet a failed poet who, envious of other people's wealth during the real-estate bubble, becomes an embezzler; a clavichordist whose dreams of art collapse under the obligations of marriage and fatherhood; and, in "Bronze," a sexually confused college freshman whose encounter with a stranger on a train leads to a revelation about his past and his future.